Finite-time shock acceleration of energetic storm particles - Chanruangrit Channok (2018)
Energetic storm particles (ESPs) of various ion species have been shown to arise from suprathermal seed ions accelerated by traveling interplanetary (IP) shocks. The observed spectral rollovers at ∼0.1-10 MeV nucleon-1 can be attributed to the finite time available for shock acceleration. Using the locally measured shock strength parameters as inputs, the finite-time shock acceleration model can successfully fit the energy spectra of carbon, oxygen, and iron ions measured by the Ultra Low Energy Isotope Spectrometer (ULEIS) on board the Advanced Composition Explorer (ACE) during three ESP events. The inferred scattering mean free path in the acceleration region ranges from a typical IP value for the weakest ESP event down to 3.0 × 10-3 AU for the strongest event. This is consistent with the idea that proton-amplified waves result from the very intense particle fluxes in major events. © 2005. The American Astronomical Society. All rights reserved.